Production design: The atmosphere and aesthetics of pan’s labyrinth applied to a photography series our word - Jezabel Guerrero Ledesma; Natalia Gurieva (ХНУРЕ, 2022)
The aim of the following investigation is to apply results of semantic analysis of some scenes of Pan’s Labyrinth in a photography series: in a stage of pre -production, production, and post-production.
Keywords: design; photography series